2018
DOI: 10.1051/e3sconf/20184002017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vegetation on flows and sediment transport

Abstract: Vegetation is a common feature in natural coastal and riverine waters, interacting with both water flow and sediment transport. However, the physical processes governing these interactions are still poorly understood, which makes it difficult to predict sediment transport and associated morphodynamics in a vegetated environment. In this context, an experimental study was conducted in laboratory with a movable bed trapped in artificial vegetation. The experimental flume is a rectangular open channel 5.75 m long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Zhao et al (2016) found that overland flow through vegetation stems was affected by grain resistance and vegetation resistance, and the latter was the predominant roughness element, accounting for 80% of the total resistance. Subsequently, Romdhane et al (2018) further confirmed these findings by conducting experiments on an erodible bed with artificial vegetation and concluded that the trapping of sediment by vegetation was attributed to the reduction of the bed shear stress since the drag force due to vegetation was the dominant flow resistance. In addition, some scholars have quantified the two resistance components by modifying Manning's roughness coefficient equation.…”
Section: Introductionmentioning
confidence: 91%
“…Zhao et al (2016) found that overland flow through vegetation stems was affected by grain resistance and vegetation resistance, and the latter was the predominant roughness element, accounting for 80% of the total resistance. Subsequently, Romdhane et al (2018) further confirmed these findings by conducting experiments on an erodible bed with artificial vegetation and concluded that the trapping of sediment by vegetation was attributed to the reduction of the bed shear stress since the drag force due to vegetation was the dominant flow resistance. In addition, some scholars have quantified the two resistance components by modifying Manning's roughness coefficient equation.…”
Section: Introductionmentioning
confidence: 91%
“…Given their significance, still regarding the processes in the gutters, the theme has also been investigated in the context of natural channels with natural succession (GURNEL ET AL, 2006;NEPF;GHISALBERTI, 2008;STOFFEL;WILFORD, 2011;CURRAN;HESSION, 2013;HUAI, 2021). Therefore, studies have addressed environments with anthropic control (ADITYA et al, 2010;CHESTER;ROBSON, 2013), artificial channels (SABBATINIA et al, 1998;SILVA, 2018;ERRICO et al, 2020), and laboratory research for simulating vegetation in test channels (ROMDHANE, et al 2018;LI et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Given their significance, still regarding the processes in the gutters, the theme has also been investigated in the context of natural channels with natural succession (GURNEL ET AL, 2006;NEPF;GHISALBERTI, 2008;STOFFEL;WILFORD, 2011;CURRAN;HESSION, 2013;HUAI, 2021). Therefore, studies have addressed environments with anthropic control (ADITYA et al, 2010;CHESTER;ROBSON, 2013), artificial channels (SABBATINIA et al, 1998;SILVA, 2018;ERRICO et al, 2020), and laboratory research for simulating vegetation in test channels (ROMDHANE, et al 2018;LI et al, 2022).…”
Section: Introductionmentioning
confidence: 99%